Collegiality in Teaching: Perceptions and Experiences of Beginning Teachers in India - Latha K.; Sarangapani, Padma M. (Voices of Teachers and Teacher Educators, 2018)
The collegiality refers to cooperation among colleagues. Studies indicate the concept of collegiality is complex and has different facets. In practice especially in the context of beginner teachers, collegiality is not just limited to, but goes beyond cooperation to include overcoming solitude, seeing support from fellow teachers, dealing with workplace issues including developing a sense of belonging and dealing with conflict, authority and bureaucracy. The Indian discourse on teachers is dominated by the idea of an isolated, meek dictator, enmeshed in administrative hierarchy but professionally alone. There is a tacit assumption that given the low status of the profession and poor quality of professional education, that workplace relationships will be casual or friendships. This paper presents findings relating to perceptions and experiences of collegiality of beginning teachers in India, based on an interview based qualitative study of 25 beginner teachers in the state of Karnataka, India. Collegiality is found to be a major theme in beginning teachers’ narratives of their workplace experience, playing a significant role in both personal and professional matters. Differences on account of age of the teacher and context of management are found. The teachers’ narratives provide a nuanced understanding of the workplace in relation to peers, seniors and the school head and contribute to a more holistic understanding of teacher development and of the Indian school as a workplace.